Human aspects of IT for the aged population. healthy and active aging : second International Conference, ITAP 2016, held as part of HCI International 2016 Toronto, ON, Canada, July 17-22, 2016, Proceedings /: healthy and active aging : second International Conference, ITAP 2016, held as part of HCI International 2016 Toronto, ON, Canada, July 17-22, 2016, Proceedings. Part II : (2016) - Unknown
No abstract available